Effects of straw mulching on microclimate characteristics and evapotranspiration of drip-irrigated winter wheat in North China Plain - Wang, Jiandong; Zhang, Yanqun; Gong, Shihong; Xu, Di; Snyder, Richard; Chen, Yanyu; Zhao, Yuefen; Yan, Qinghong (International Journal of Agricultural and Biological Engineering, 2018)
Field experiments were conducted for two consecutive years (2013–2014 and 2014–2015) to study the effects of straw mulching on microclimate characteristics, energy flux, soil evaporation (Es) and evapotranspiration of winter wheat (Triticum aestivum L.) under adequate drip irrigation in North China Plain (NCP). The results revealed that straw mulching affected air temperature (Ta) and dew point temperature (Td) near the soil surface but had little effect on relative humidity (RH) compared with non-mulched fields. Straw mulching increased the turbulent exchange coefficient (K), and K within the canopy was higher than that above the canopy. Straw mulching clearly increased the sensible heat flux (H) distribution in April–June, and part of the energy needed for evapotranspiration was provided by transfer from the warmer air aloft. There was a linear functional relationship between H and Ta measured above and within the canopy. The straw mulching decreased Es but increased crop transpiration (T). Mulched treatment (TM) can decrease the total irrigation amount by about 7%-15% compared with the non-mulched treatment (TN). There were no significant differences (p>0.05) in cumulative crop evapotranspiration (ETc) between TM and TN treatments under adequate drip irrigation, and the use of mulch may need to be combined with an optimal deficit drip irrigation schedule for managing the declining water table in NCP. Keywords: drip irrigation, microclimate, straw mulching, winter wheat, evapotranspiration, water use efficiency DOI: 10.25165/j.ijabe.20181102.3192 Citation: Wang J D, Zhang Y Q, Gong S H, Xu D, Snyder R, Chen Y Y, et al. Effects of straw mulching on microclimate characteristics and evapotranspiration of drip-irrigated winter wheat in North China Plain. Int J Agric & Biol Eng, 2018; 11(2): 122–131.